Estudo comparativo dos efeitos da metilcelulose a 2% e 4% sobre as células endoteliais corneanas de pacientes submetidos à facoemulsificação - Holanda, Andréa Gifoni Siebra de (2012)
Modern cataract surgery in normal corneas, independent of the surgical technique used, causes a mean 10 to 20% loss of endothelial cells. Viscoelastic substances were developed with the function of maintaining the natural spaces of the eye and providing mechanical protection to the intraocular structures during surgery. The objective of this study was to perform a comparative analysis of the effect of two viscoelastic compositions, methylcellulose 2% and 4%, in corneal endothelial protection against secondary damage to the phacoemulsification procedure. We performed a prospective, randomized, double-blind study with senile cataract patients, submitted to phacoemulsification surgery with intraocular lens (IOL) implant. All patients were submitted to a complete ophthalmological assessment, including specular microscopy. After initial assessment, the patients were randomized into two groups: in Group A (n=63) we used methylcellulose 2%, and in Group B (n=63) methylcellulose 4%. There was no statistically significant difference for the parameters analyzed between groups before surgery. However, at 30 days after surgery, mean density of endothelial cells (DCE) was 2128.78±277.55 cells/mm² in Group A and 2395.79±262.16 cells/mm² in Group B, representing a 15.15 and 6.76% loss of endothelial cells in Groups A and B, respectively. Mean DCE was significantly reduced (p<0.05), in both the inter- and inter-group analysis on the 1st, 15th, and 30th day after surgery. ECC increased on the 1st day after surgery in group A, this datum was statistically significant (p<0.05). There was no statistical difference for the other parameters assessed. In this study, we conclude that, despite the advantages of methylcellulose 4% over 2% in regards to the reduction of endothelial cell loss after phacoemulsification, both viscoelastic substances are similar in relation to clinical parameters such as central corneal thickness, coefficient of variation in cell size and percentage of hexagonal cells, which reflect corneal preservation and maintain adequate physiological conditions for proper endothelial function. However, due to the slight difference in cost between the two products and the benefits of methylcellulose 4% on endothelial cell preservation, this may be considered a choice product in routine cataract surgery, as indications for phacoemulsification are increasingly early, due to patients’ visual demands, promoting, in this manner, healthier corneas in the long term.